Characterization and Removal Efficiency of Central Effluent Treatment Plant (CETP) - Monira, U.; Sattar, G.S.; Mostafa, M.G. (Journal of Sustainability and Environmental Management, 2023)
Tannery industries are one of the most pollution-generating industries in the world. Tannery wastewater is usually characterized by high BOD, COD, TDS, and TSS and a high percentage of dissolved organic and inorganic matter. The central effluent treatment plant (CETP) of industry plays a vital role in sustainable industrial waste management and saves different lives from harmful effects. The study aimed to analyze various physicochemical parameters of the composite tannery influent and effluent as well as the removal efficiency of the CETP of the Savar Tannery Industrial Zone in Bangladesh. It was carried out at Savar Upazila, situated in the northwest part of Dhaka, Bangladesh. The samples were collected three times (pre-monsoon, monsoon, and post-monsoon) in a year, from monsoon 2021 to pre-monsoon 2022. The major water quality parameters for the influents and effluents included pH, BOD, COD, TDS, TSS, NO3-, SO42-, HCO3-, PO43-, Cl-, Na, Ca, Cr, Fe, Cu, Zn, and Pb. Most of the parameters, especially BOD, COD, TDS, and TSS after treatment, exceeded the standard permissible limits of effluent discharge prescribed by the ISW-BDS-ECR (1997), DoE-BD, and NEQS (2000), and these values were two times higher than the permissible limit. The DO value was four times lower than the permissible limit, indicating heavily polluted water. The concentration of the cations in the tannery effluents was in the following order: Na>Ca>Cr>Fe>Cu>Zn>Pb. The analysis results illustrated that the overall removal efficiency of the CETP was about 47%. The study observed that the performance of the CETP was not satisfactory, and hence it needs further improvement in the treating capacity for sustainable industrial wastewater management.